Transitividade e passiva (Revista de Estudos da Linguagem, 1996)
This paper presents a study of passive sentences of the type SUBJECT - BE - PAST PARTICIPLE - PREPOSITIONAL PHRASE. The data include formal written Portuguese as well as spoken Portuguese elicited in interviews. The pragrnatic function of the passive conceming text organization is discussed. The gradient notion of transitivity is employed as an indicator of the portion of the text (foreground/background) where the passive tends to occur.